2021
DOI: 10.1542/neo.22-9-e600
|View full text |Cite
|
Sign up to set email alerts
|

Congenital and Perinatal Tuberculosis

Abstract: This review discusses the recent literature (2006–2020) about the epidemiology, clinical presentation, diagnosis, and management of infants with congenital or perinatal tuberculosis (TB). While the incidence of childhood TB is declining in the United States and worldwide, many case reports describe how clinical suspicion for neonatal TB is raised only if an ill-appearing neonate does not improve with broad-spectrum antibiotics. Furthermore, the delay in initiating appropriate anti-TB therapy often results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Vertical transmission from mother to neonate is also possible. 4 Interestingly, a meta-analysis of studies from 1929-2015 found that <20% of TB transmission to children was attributable to household exposures, suggesting that community exposure may be more substantial than previously considered, consistent with the mode of acquisition in this case. 5 Since pulmonary TB may be difficult to distinguish from community-acquired pneumonia, results of a recent retrospective cohort study in South Korea proposed that a delta neutrophil index (>1.0%) may be useful to rule out the possibility of pulmonary TB given its high negative predictive value, but its utility is dependent on regional prevalence.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Vertical transmission from mother to neonate is also possible. 4 Interestingly, a meta-analysis of studies from 1929-2015 found that <20% of TB transmission to children was attributable to household exposures, suggesting that community exposure may be more substantial than previously considered, consistent with the mode of acquisition in this case. 5 Since pulmonary TB may be difficult to distinguish from community-acquired pneumonia, results of a recent retrospective cohort study in South Korea proposed that a delta neutrophil index (>1.0%) may be useful to rule out the possibility of pulmonary TB given its high negative predictive value, but its utility is dependent on regional prevalence.…”
Section: Discussionsupporting
confidence: 64%
“…Chest radiography in infant TB may reveal miliary pattern (47%), multiple pulmonary nodules (11%), and lobar pneumonia (12%). 4 Patients with a miliary pattern should be evaluated for meningitis and intracranial disease. Analysis of CSF usually demonstrates lymphocytosis, low glucose, and high protein concentrations, though CNS involvement with negative CSF studies was previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fetus infected with Mycobacterium tuberculosis intrauterine or during delivery is called congenital tuberculosis, which is a rare type but might leader to a high mortality rate ( Jenkins et al, 2017 ). Literature reviewed reported no more than 400 cases in world limited treatment experience with M. tuberculosis infection ( Newberry and Robertson Bell, 2018 ; Li et al, 2019 ; Shao et al, 2021 ). Congenital tuberculosis symptoms cover respiratory, neurologic, and gastrointestinal.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital TB is an extremely rare M ycobacterium tuberculosis infection transmitted from the mother to the fetus [ 44 ] with only 300–400 reported cases [ 45 , 46 ]. Chest radiographs may be normal initially [ 44 – 48 ]. The most common reported findings which may appear after 4–8 weeks are miliary pattern, multiple pulmonary nodules, lobar pneumonia and rarely, bronchopneumonia, interstitial pneumonia and mediastinal lymphadenopathy [ 45 , 46 , 48 ].…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Chest radiographs may be normal initially [ 44 – 48 ]. The most common reported findings which may appear after 4–8 weeks are miliary pattern, multiple pulmonary nodules, lobar pneumonia and rarely, bronchopneumonia, interstitial pneumonia and mediastinal lymphadenopathy [ 45 , 46 , 48 ]. Ultrasound may show hypoechoic foci in the liver or spleen, ascites and abdominal lymphadenopathy.…”
Section: Imaging Modalitiesmentioning
confidence: 99%